Kedudukan Konsultan Hukum Hak Kekayaan Intelektual dalam Pendaftaran Hak Paten - I Nyoman Mahendra Guna; Johannes Ibrahim Kosasih; I Made Aditya Mantara Putra (Warmadewa Press, 2022)
The 1945 Constitution of the Republic of Indonesia clearly states that the State of Indonesia is a state of law. If an invention or work, it must be identical to a patent that is then filed by an Intellectual Property Consultant. What is meant by this patent is that it must belong to the inventor or creator. Therefore, researchers want to know more about the above, which can be formulated. The problem is about the legal arrangement of the position of intellectual property rights consultants in the registration of patent rights according to patent law and legal consequences if there is a violation by an intellectual property rights consultant in the registration of patent rights. This research uses a normative type, namely research by analyzing literature based on the legal materials used. The legal basis for intellectual property rights consultants is regulated in the Government Regulation of the Republic of Indonesia Number 2 of 2005 concerning Intellectual Property Rights Consultants. The use of a person's patent rights without permission has an impact on legal consequences and can be entangled in accordance with the articles in Law Number 13 of 2016 concerning Patents.